2007
DOI: 10.1289/ehp.10289
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Matrix Metalloproteinase-9 in Ozone-Induced Airway Inflammation

Abstract: BackgroundExposure to ozone causes airway inflammation, hyperreactivity, lung hyper-permeability, and epithelial cell injury. An early inflammatory response induced by inhaled O3 is characterized primarily by release of inflammatory mediators such as cytokines, chemokines, and airway neutrophil accumulation. Matrix metalloproteinases (MMPs) have been implicated in the pathogenesis of oxidative lung disorders including acute lung injury, asthma, and chronic obstructive pulmonary disease.ObjectiveWe hypothesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 60 publications
9
43
0
Order By: Relevance
“…Beklen et al (7) showed that there was an upregulation of both MMP9 and IL-8 in periodontitis. Many studies related with airway epithelium have shown a direct link between the IL-8 secretion and MMP9 expression (15,31,55). Yoon et al (55) have shown that MMP9 protects from ozone induced airway injury may be via posttranscriptional effects on IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…Beklen et al (7) showed that there was an upregulation of both MMP9 and IL-8 in periodontitis. Many studies related with airway epithelium have shown a direct link between the IL-8 secretion and MMP9 expression (15,31,55). Yoon et al (55) have shown that MMP9 protects from ozone induced airway injury may be via posttranscriptional effects on IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…BAL from MMP9-deficient mice exposed to ozone had increased protein content and greater numbers of neutrophils and epithelial cells compared to wild-type mice; this finding points to a protective role of MMP9 in ozone-induced inflammation [35]. This protective effect was not observed in MMP7-deficient mice [35]. It is important to note that, although often neglected by the authors, none of the presented MMP9 inhibition strategies was specific for MMP9 ( fig.…”
Section: Acute Lung Injurymentioning
confidence: 94%
“…Inhibition of MMP9 activity with doxycycline reduced pancreatitis-associated lung injury and diminished expression of MMP9 in pulmonary tissue [69]. BAL from MMP9-deficient mice exposed to ozone had increased protein content and greater numbers of neutrophils and epithelial cells compared to wild-type mice; this finding points to a protective role of MMP9 in ozone-induced inflammation [35]. This protective effect was not observed in MMP7-deficient mice [35].…”
Section: Acute Lung Injurymentioning
confidence: 99%
“…Since 2005, there have been a number of key experimental animal studies carried out in mice that demonstrated acute inflammation and airway injury following acute (Damera et al, 2010) or sub-chronic exposure (Inoue et al, 2008;Yoon, Cho & Kleeberger, 2007) to environmentally pertinent ozone concentrations in the range 100-300 ppb. Additional subchronic and chronic ozone exposure studies (500 ppb) in rhesus monkeys have demonstrated structural changes in the distal and proximal airways (Fanucchi et al, 2006;Carey et al, 2011) and allergy-like patterns of response (increased globlet cells and eosinophils) to allergen and ozone co-challenges (Kajekar et al, 2007;Miller et al, 2009;van Winkle et al, 2010;Plopper et al, 2007).…”
Section: Experimental and Panel Studiesmentioning
confidence: 99%